PERAN DUKUNGAN SOSIAL KELUARGA TERHADAP KEBERMAKNAAN HIDUP PASIEN HEMODIALISA DI RUMAH SAKIT : The Role of Family Social Support on The Meaningfulness of Life of Hemodialysa Patients in The Hospital - Amseke, Fredericksen Victoranto; Nunes, Bernadita; Riada, Marleny Rambu (Yayasan Al-Amin Qalbu, 2025)
The meaning of life is an individual's appreciation of their own existence, especially hemodialysis patients who feel they are valuable and have a purpose in life. One of the influencing factors is family social support as a support system that provides meaning to keep fighting in life. The aim of this research was to determine the effect of family social support on the meaningfulness of life of hemodialysis patients at Hospital X in Kupang City. The method in this research is quantitative. The data collection tool uses a questionnaire. Participants in this study were 40 hemodialysis patients at Hospital X in Kupang City. The data analysis technique uses simple linear regression analysis. The results of this study show that there is a positive and significant influence of family social support on the meaningfulness of life of hemodialysis patients at Hospital